2020
DOI: 10.3390/app10217727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking, Druglikeness Analysis, and ADMET Prediction of the Chlorinated Ethanoanthracene Derivatives as Possible Antidepressant Agents

Abstract: Ethanoanthracene cycloadducts (5–7) anti, (5–7) syn, and (5–7) dec have been synthesized from the Diels–Alder (DA) reaction of diene 1,8-dichloroanthracene 2, with the dienophiles; acrylonitrile 3, 1-cynavinyl acetate 4, and phenyl vinyl sulfone 5, individually. The steric effect of dienophile substituents were more favorable toward the anti-isomer formation as deduced from 1H-NMR spectrum. The cheminformatics prediction for (5–7) antiand (5–7) syn was investigated. The in silico anticipated anti-depression ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
0
11
0
1
Order By: Relevance
“…Analysis of the pharmacokinetics and drug-likeness features such as molecular weight (< 500 g/mol), number of hydrogen bond donor (not > 5), number of H-bond acceptor (< 10), bioavailability (> 10%), and octanol-water partition coefficient log P (not >5) showed that orientin had two violations exceeding the acceptable limit in the number of H-bond donor (8) and acceptor (11) while ursolic acid has one violation (Table 4). Druglikeness is a measure of similarity between certain compound and standard drug as evaluated based on molecular properties (such as hydrogen bonding, hydrophobicity, ) and structural merits [60,61]. A vital index at predicting the worthiness of a compound as a drug candidate is Lipinski rule of five, which basically indicates that a compound will possibly exhibit poor bioavailability if it violates the five rules [62].…”
Section: Pharmacokinetics Investigationmentioning
confidence: 99%
“…Analysis of the pharmacokinetics and drug-likeness features such as molecular weight (< 500 g/mol), number of hydrogen bond donor (not > 5), number of H-bond acceptor (< 10), bioavailability (> 10%), and octanol-water partition coefficient log P (not >5) showed that orientin had two violations exceeding the acceptable limit in the number of H-bond donor (8) and acceptor (11) while ursolic acid has one violation (Table 4). Druglikeness is a measure of similarity between certain compound and standard drug as evaluated based on molecular properties (such as hydrogen bonding, hydrophobicity, ) and structural merits [60,61]. A vital index at predicting the worthiness of a compound as a drug candidate is Lipinski rule of five, which basically indicates that a compound will possibly exhibit poor bioavailability if it violates the five rules [62].…”
Section: Pharmacokinetics Investigationmentioning
confidence: 99%
“…Many drug candidates fail due to their high cytotoxicity. [25,26] Therefore we evaluated the toxicity risks of all compounds by using Osiris property explorer (Table S3). Especially compounds 2m, 2g, 2k, 3e and 3l showed no toxicity regarding mutagenicity, tumorigenicity, irritant effect and effect on the reproductive system (Table 4).…”
Section: In Silico Admet Propertiesmentioning
confidence: 99%
“…Then, a ligand toxicity test was carried out using Data Warrior software. Several studies have used this software to find new medicinal compounds, such as cancer and antidepressant drugs [37][38]. The results of the predictive analysis of ligand toxicity using Data Warrior are shown in Table 5 [39].…”
Section: Prediction Of Ligand Toxicitymentioning
confidence: 99%